CHROMITITES OF ULTRAMAFIC COMPLEXES OF THE VALIZHGEN PENINSULA, KORYAK HIGHLAND - Osipenko A.B.; Sidorov E.G.; Kostoyanov A.I.; Tolstykh N.D. (My University, 2002)
This paper covers the results of a study of ore and accessory chromite mineralizations in an ultramafic rock complex of the Valizhgen Peninsula. It was found that the chromite mineralization belongs to the podiform type, is located in lens-shaped dunite bodies, and is represented by several structural-textural varieties. The ore and accessory chrome-spinellides have some specific compositional features in the rocks of either series distinguished as follows: chrome-spinellides of the cumulative dunite-orthopyroxenite-chromitite series have elevated Cr, Ti, and Fe3+ contents, while spinellides from residual harzburgites are typically low in TiO2 and Fe2O3 and variable in Cr and Mg contents. The specific location of chromitites in mafic-ultramafic massifs of the peninsula and the composition of ore and accessory chrome-spinellides from ultramafics can be accounted for by an interaction of primitive mantle magmas with host harzburgites. The calculations using mineral thermobarometry indicate a relatively low pressure and high temperature and oxygen fugacity during the formation of chromite mineralization. The chemical and Re-Os isotopic compositions were also studied for platinum group element (PGE) minerals from placers of the Valizhgen Peninsula. It is suggested that chromitites of the mafic-ultramafic massifs are sources of these placers.